Hak Asasi Manusia Perspektif Al-Qur'an: Menjawab Isu Kemanusiaan Masa Kini - Anisatul Faizah; Kusnadi; Aristhopan Firdaus (Journal of Literature Review, 2025)
This study examines the concept of human rights from the Qur'anic perspective through a thematic interpretation approach (maudhu'i). The research aims to analyze the concept of human rights in the Qur'an, identify related verses, and evaluate their relevance to contemporary humanitarian issues. The method used is thematic interpretation with steps: theme determination, verse identification, linguistic analysis, inter-verse correlation, and synthesis. The results show that the Qur'an contains 147 verses about human rights spread across 89 surahs, covering ten main categories: right to life, right to dignity, right to justice, right to equality before the law, right to choose, right to expression, right to privacy, right to property, right to basic needs, and right to education. The concept of human rights in the Qur'an is based on karamah al-insan (human dignity) which is universal and aligned with the principles of maqasid al-syari'ah. This study concludes that the concept of human rights in Islam is not contrary to the universal declaration, but rather provides a unique contribution by balancing spiritual-material dimensions and rights-obligations, which is relevant to addressing contemporary challenges such as digital privacy, environmental issues, and refugee rights.